Max is missing (Trinity Pictures, 1995)
Max is forced to vacation in Peru with his historian dad and his new girlfriend. During a hike through some South American ruins, Max escapes from his dad's childish romantic behaviour to explore on his own. During his independence, a strange man give Max a priceless relic and explains he must not let it fall into the wrong hands. Max soon finds himself being followed by two suspicious men. therefore, Max seeks help from a local teenager to help him outsmart the follower. The two boys find themselves on an adventure of a lifetime when they discover they hold the power to a million dollar treasure.